Addition of high-dose methotrexate to standard treatment for patients with high-risk diffuse large B-cell lymphoma contributes to improved freedom from progression and survival but does not prevent central nervous system relapse. Issue 8 (3rd July 2019) - Goldschmidt, Neta; Horowitz, Netanel A.; Heffes, Vered; Darawshy, Fares; Mashiach, Tatiana; Shaulov, Adir; Gatt, Moshe E.; Dann, Eldad J.
Abstract: Combination of rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) is regarded as standard care for diffuse large B-cell lymphoma (DLBCL) and upfront intensification of therapy is still controversial. The current study aimed to dertermine whether the addition of high-dose methotrexate (HDMTX) affects long-term outcomes and could also prevent central nervous system (CNS) relapse. Medical records of 480 patients with DLBCL treated between 1994 and 2013 at Rambam and Hadassah medical centers in Israel were reviewed; 130 (27%) had received HDMTX. Patients receiving HDMTX generally had higher International Prognostic Index (IPI) and CNS-IPI scores. HDMTX addition significantly improved progression free and overall survival ( p = .001) and this advantage was maintained in multivariate analysis (HR for OS 0.3; 95% CI 0.19–0.47; p < .0001). Thirty-one (6.5%) patients had CNS relapse and in these cases high CNS-IPI, but not HDMTX treatment, was independently associated with CNS relapse (HR 1.2; 95% CI 1.2–11.5; p = .02). In conclusion, the addition of HDMTX to CHOP/RCHOP independently and significantly improved prognosis of patients with high-risk DLBCL, irrespective of their risk for CNS relapse.